EMBODIED IDENTITIES AND POSITIONAL CHOICES: HOW TATTOOEES CONSTRUCT IDENTITY AND NEGOTIATE A TATTOOED STATUS WITHIN SOCIETY - Nichols, Hayley; Foster, Don (PINS-Psychology in Society, 2026)
This study was concerned with the ideological implications of taking on a tattooed status within a hegemonic order that proscribes the limits of bodily expression. A discourse analysis method was used to draw out the ways in which seventeen tattooees made meaning of, and justified, the adoption of a tattooed status, and negotiated everyday life as a visibly marked individual. Participants were interviewed by means of individual interviews, a focus group discussion, and internet correspondence. All represented their choice to become tattooed primarily in terms of an individualist discourse; however, several used their tattoos to augment subcultural identities, thus using their tattoos to express shared values and norms as well as to consolidate personal experience. Participants attempted to create positive social identities as tattooees by stigma management strategies such as dissociating themselves from negative stereotypes, constructing tattoos as a legitimate art form, and intensifying a rebellious stance towards the hegemonic order.